Pengaruh Tingkat Pendidikan, Pemahaman Akuntansi, dan Tingkat Kesiapan UMKM terhadap Implementasi Standar Akuntansi Keuangan Entitas Mikro Kecil dan Menengah dengan Lama Usaha Sebagai Variabel Moderasi : (Studi pada Kelurahan Waioti) - Saputripuspita Victoria; Konstantinus Pati Sanga; Wilhelmina Mitan (Akuntansi dan Ekonomi Pajak: Perspektif Global, 2024)
This study aimed to analyze the influence of education level, accounting understanding, and MSME readiness on the implementation of Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM), with business age as a moderating variable. The study employed a quantitative method. The population comprised MSME actors in Waioti Village, totaling 44 individuals. Sampling was conducted using a saturated sampling technique, resulting in 44 respondents. The data used in this study were primary data, collected through questionnaires measured on a Likert scale. Data analysis utilized multiple linear regression and moderated regression analysis, along with descriptive statistics, data quality tests, classical assumption tests, and hypothesis testing. The results indicated that: (1) Education level did not influence the implementation of SAK EMKM, (2) Accounting understanding significantly influenced the implementation of SAK EMKM, (3) Readiness did not affect the implementation of SAK EMKM. (4) Business age influenced the implementation of SAK EMKM, (5) Business age did not moderate the effect of education level on the implementation of SAK EMKM, (6) Business age negatively moderated the effect of accounting understanding on the implementation of SAK EMKM. (7) Business age did not moderate the effect of MSME readiness on the implementation of SAK EMKM.